A 'NAC' for targeting proteins to the ER. Issue 9 (September 2022) - Coelho, João P.L.; Shao, Sichen
Abstract : The signal recognition particle (SRP) cotranslationally targets a large and diverse portion of the nascent proteome to the endoplasmic reticulum (ER). A recent study by Jomaa et al. reveals an unexpected function for the ribosome-bound nascent chain-associated complex (NAC) in sensing ER-targeting signals and recruiting SRP to the appropriate ribosomes for high-fidelity targeting.